(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Improving methods of measuring, managing, and making decisions on regional water resources became necessary due to rising water use, pollution, and urbanization rates, as well as the effects of climate change. In the same vein as ecological and carbon footprints, the notion of water footprint (WF) has just recently made its way into the scientific literature. An item’s water footprint (WF) is the sum of all the water resources that are either used up or polluted in some way throughout its manufacturing. This is the first research to examine the blue and green water footprints of agricultural output in Al-najaf governorate, southern Iraq, from 2013 to 2023, and to explore the impact on the governorate’s water supply. We have employed the recently created WF technique. Crop water requirement (CWR) in CROPWAT 8.0 software was used to determine the quantities of blue and green evapotranspiration. Use of statistical data has been made, which includes data on weather, rainfall, local crop coefficients, cultivation area, crop production quantities, and animal statistics. For the period from 2013 to 2023, the average yearly agricultural water flow (WF) in the Al-Najaf governorate was calculated to be 1,315,201,621 Mm3/yr. Agriculture uses the most water of all economic activities (56%). Consumption of water is mostly caused by cereal and feed crops. The most important crops grown using water from rivers are rice and wheat, which together account for over half of all WF. Just 12% of agricultural WF goes into vegetable cultivation. Just 16% of the WF for crop production was green. Broiler chickens account for 42% of all animal production water demand, while dairy cattle account for 35%. There is plenty of arable land in the research region. Unfortunately, the region’s paucity of water supplies and other factors hinder agricultural activity. Cutting back on WF and blue water content might help the governorate’s freshwater supplies last longer. Authorities at the national level should be able to use this study to inform the creation of more precise policies for the management of irrigation water.